2017
DOI: 10.1371/journal.pone.0186686
|View full text |Cite
|
Sign up to set email alerts
|

TDF and quantitative ultrasound bone quality in African patients on second line ART, ANRS 12169 2LADY sub-study

Abstract: BackgroundBone demineralization, which leads to osteoporosis and increased fracture risk, is a common metabolic disorder in HIV-infected individuals. In this study, we aimed to assess the change in bone quality using quantitative ultrasound (QUS) over 96 weeks of follow-up after initiation of second-line treatment, and to identify factors associated with change in bone quality.Methods and findingsIn a randomized trial (ANRS 12169), TDF and PI-naïve participants failing standard first-line treatment, from Burki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Two of the included studies reported on some individuals with anemia. The studies showed no evidence of statistical heterogeneity ( I 2 = 0%; p > 0.05) 16, 17 . The included studies likely have a relatively small sample size (RR=1.66, 95% CI (1.02 – 2.70); I 2 = Not estimated, 2 trials, very low certainty of the evidence).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Two of the included studies reported on some individuals with anemia. The studies showed no evidence of statistical heterogeneity ( I 2 = 0%; p > 0.05) 16, 17 . The included studies likely have a relatively small sample size (RR=1.66, 95% CI (1.02 – 2.70); I 2 = Not estimated, 2 trials, very low certainty of the evidence).…”
Section: Resultsmentioning
confidence: 88%
“…Two authors (FT and GE) independently read the titles and abstracts and excluded 92 studies because they did not meet the inclusion criteria. Four studies met the inclusion criteria as shown in Figure 1, Table 1 [14][15][16][17] . The four studies were carried out in health facilities within low-and middle-income countries.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations